2011
DOI: 10.1002/sia.3870
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the detection system in the soft X‐ray absorption spectroscopy

Abstract: A unique soft X-ray absorption spectroscopy detection system has been developed for depth profiling analysis of a sample with combined different detection methods: total electron yield, partial electron yield (PEY), and partial fluorescent X-ray yield. We found that a PEY spectrum measured with a conventional microchannel plate detector is sometimes deformed by inclusion of unexpected fluorescent X-rays. In this system, a new PEY detector has been designed and constructed to overcome the aforementioned problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…Partial electron yield is the measurement of that portion of the photoelectrons that are emitted by the sample and collected by the hemispherical analyzer, whereas the drain current measures that portion of the photoelectrons that are generated in the sample and subsequently earthed. The partial electron yield is likely to be more surface sensitive . There are subtle differences between these two sets of spectra, however, the essential diagnostic features are the same.…”
Section: Resultsmentioning
confidence: 99%
“…Partial electron yield is the measurement of that portion of the photoelectrons that are emitted by the sample and collected by the hemispherical analyzer, whereas the drain current measures that portion of the photoelectrons that are generated in the sample and subsequently earthed. The partial electron yield is likely to be more surface sensitive . There are subtle differences between these two sets of spectra, however, the essential diagnostic features are the same.…”
Section: Resultsmentioning
confidence: 99%
“…In their studies, various probe depths were obtained by collecting the emitted electrons at various detection angles. Subsequent studies showed that the probe depth could be changed by the application of a retarding voltage and the use of a PEY detector based on the MCP [4,14]. However, in these cases, specially designed experimental setups were required.…”
Section: Introductionmentioning
confidence: 95%
“…This indicates that electrons originating from the deeper regions of the material lose more energy upon reaching the surface and suggests that the probe depth can be changed by selecting the energy of the detected electrons. In the EY mode, the partial EY (PEY) mode detects the electrons emitted from the sample surface and is surface sensitive compared with the total EY (TEY) mode that measures the sample drain current [4]. Amemiya et al [12,13] developed a depth-resolved XAS technique in X-ray magnetic circular dichroism, using an imaging-type multichannel plate (MCP) detector.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Partial electron yield (PEY), which is used to detect electrons escaping from material surfaces, has been proposed as a surface-sensitive method (Brennan et al, 1981;Stö hr, 1979;Nakanishi & Ohta, 2012). One particular method for detecting Auger electrons with elemental-specific energy is called Auger electron yield (AEY) (Citrin et al, 1978;Brennan et al, 1981).…”
Section: Introductionmentioning
confidence: 99%